Management of cerebral vasospasm following aneurysmal subarachnoid hemorrhage - Mohamed Shehabeldin; Yazan Alderazi (Southwest Respiratory and Critical Care Chronicles, 2017)
Cerebral vasospasm is a serious complication following aneurysmal subarachnoid hemorrhage (SAH); it causes delayed cerebral ischemia (DCI) or infarction. Arterial vasospasm is considered the most common cause of disability and mortality among survivors of aneurysmal SAH. Monitoring for vasospasm is extremely important starting from the first day following a hemorrhage. The mechanism of vasospasm is not completely understood, but most data and studies link the incidence of vasospasm to inflammatory responses secondary to extravasation of blood into the subarachnoid space. It is essential for critical care teams and health care providers caring for patients with aneurysmal SAH to understand the clinical presentation and management of cerebral vasospasm. In our review, we focus on the guidelines for monitoring and basic management of vasospasm and DCI which include monitoring options, hemodynamic and endovascular therapy, triggers for intervention, and triggers for treatment de-escalation.